2008
DOI: 10.1149/1.2943258
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Electrode Materials for Li-air Cells

Abstract: In this paper, carbon nanotubes (CNTs) have been investigated as oxygen cathode materials used for Li-oxygen/air cells and compared with carbon black (CB), graphite (G), and active carbon (AC). Both multi wall nanotube (MWNT) and single wall nanotube (SWNT) showed advantage when compared with other types of carbonaceous materials. The higher discharge capacity of CNTs than AC is explained by the exposed surface area surface area. SWNT is very promising as a cathode material in terms of higher cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Porous carbons are generally considered as defective crystallites of graphite. 355 To date, various carbons such as activated carbon, carbon nanotubes, Super P, Ketjen Black, Vulcan XC-72 4,5,59,124,216,244,356,357 have been used in Li-O 2 batteries. Yang et al 358 reported a the comparison of the physical parameters and specific capacities of various carbons as listed in Table 3.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Porous carbons are generally considered as defective crystallites of graphite. 355 To date, various carbons such as activated carbon, carbon nanotubes, Super P, Ketjen Black, Vulcan XC-72 4,5,59,124,216,244,356,357 have been used in Li-O 2 batteries. Yang et al 358 reported a the comparison of the physical parameters and specific capacities of various carbons as listed in Table 3.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Various kinds of cathode materials have been investigated to reduce potential hysteresis and thus to improve the round-trip efficiency of Li–oxygen batteries. The materials include nanostructured carbons, metals, transition-metal oxides, transition-metal nitrides, , and transition-metal carbides. All of the investigated catalysts have limitations such as low onset potentials, low limiting currents, and poor stabilities under nonaqueous conditions, and the battery performances need to be improved further to make Li–O 2 battery technology reliable. Studies on cathode electrocatalysts have indicated that the charge voltage, the discharge capacity, and the capacity retention are substantially dependent on the type of electrocatalyst used at the cathode, the selection of the electrolyte, and experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…20 Up to now, various commercially available carbons, including activated carbon (AC), Vulcan XC-72, Ketjen Black (KB), carbon nanotubes (CNTs), Super P, etc. [21][22][23][24][25][26][27][28] have been employed in LABs. Yang et al compared the physical parameters and specific capacities of several carbons, 29 as shown in Table I.…”
mentioning
confidence: 99%